Architecture for Decision Support in Precision Livestock Farming - Gomes, Jonas S.; David, José Maria N.; Braga, Regina; Ströele, Victor; Arbex, Wagner; Barbosa, Bryan; Gomes, Wneiton Luiz; Fonseca, Leonardo M. Gravina (Anais do Brazilian e-Science Workshop (BreSci), 2021)
The use of sensors in the agricultural domain generates a massive volume of heterogeneous data that must be treated, stored, and processed for decision-making. These decisions must be taken considering the diversity of devices and contextual information, which is often not considered but is important to the decision-making process. This paper presents an architecture to integrate data from sensors related to precision livestock farms. The integration and processing of these data can support decision-making, lead to more accurate results and enhance agribusiness sustainability.